¿La Auditoria De Sistemas Como La Profesión Infaltable En Una Organización? (2023)
The Systems Audit is a process of evaluation, verification, validation and compliance, which is responsible for diagnosing, identifying the activities that are carried out in the areas of the organizations and with greater emphasis on the areas of technology. Although in the 21st century, these areas have taken on relevant importance, because organizations, in order to evaluate their processes, and see how their internal X-ray is, and try to minimize the risk, have chosen to have the audit of systems, whether internal or external.